Film formation and surface growth on tin electrodes in bicarbonate solutions: an impedance spectroscopy study - Bonilla, S. H.; Rodriguez, J.; Zinola, C. F.; Bello, C.; Giannetti, B. F. (Elsevier B.V., 2005)
The electrochemical behaviour of potentiodynamically formed thin anodic films of polycrystalline tin in aqueous sodium bicarbonate solutions (pH approximate to 8.3) were studied using cyclic voltammetry and electrochemical impedance spectroscopy. Different equivalent circuits corresponding to various potential regions were employed to account for the electrochemical processes taking place under each condition. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: tin; EIS; cyclic voltammetry; anodic film